Praktik Mediasi Rasulullah SAW (SULH) Dalam Penyelesaian Konflik Antar Kelompok - Tusriyanto, Tusriyanto; Basri, Basri (Pascasarjana IAIN Metro, 2024)
The purpose of this research is to describe the mediation practices of the Prophet Muhammad SAW in resolving inter-group conflicts in Balinuraga, South Lampung. The presence of a diverse society is Indonesia's wealth that must be recognized, accepted, and respected, then realized in the motto